Genome-wide linkage analysis of von Willebrand factor plasma levels: results from the GAIT project - Carlos Souto, Juan; Almasy, Laura; Manuel Soria, Jose; Buil, Alfonso; Stone, William; Lathrop, Mark; Blangero, John; Fontcuberta, Jordi (Thrombosis and Haemostasis, 2003)
High plasma levels of von Willebrand factor (vWF) have been associated with the risk of thromboembolic disease. As a complex trait, this phenotype must be influenced by genetic and environmental factors. Among the genetic factors, only the ABO gene located on chromosome 9q34 has been clearly linked to the plasma levels of vWF. This locus explains about 30-40% of the genetic variability. Therefore, the source of the majority of the genetic component remains to be identified.To search for these unknown loci, we conducted a genome-wide linkage screen for genes affecting normal variation in vWF levels in 21 Spanish families as part of the GAIT (Genetic Analysis of Idiopathic Thrombophilia) Project.The results showed that the strongest linkage signal (LOD = 3.46, p = 0.00003) for vWF was found on chromosome 9q34 at the DNA marker D9S290, where the ABO gene is located. Additional suggestive linkage signals were found on chromosomes 2q23.2 (LOD = 1.65, p = 0.003) and 1p36.13 (LOD = 1.32, p = 0.007). After refining the linkage analysis, conditional to the ABO genotype, three additional loci on chromosomes 5, 6 and 22 showed LOD scores higher than 1, suggesting the presence of other genes linked to vWF levels. Curiously, no linkage signals were detected in other chromosome regions previously associated with vWF levels (like the structural VWF gene on 12p13.2 or Lewis blood group gene on 19q13). These results indicate that these loci are not important genetic determinants of the normal variation of vWF levels.Our results indicate that the ABO locus is the major genetic determinant of the plasma levels of the vWF in Spanish population. It is possible that there are other potential regions on chromosomes 1, 2, 5, 6 and 22 that influence this thrombosis risk factor. However, the structural vWF gene itself has a very low influence (if any) on the plasma levels of vWF.
Keywords: ABO blood group; genome-wide linkage analysis; von Wille-brand factor